Morphological diversity, total phenolic and flavonoid content of Echinacea purpurea cultivated in Karangpandan, Central Java, Indonesia - Dwi Fajar Sidhiq; YULI WIDIYASTUTI; DYAH SUBOSITI; BAMBANG PUJIASMANTO; Ahmad Yunus (Society for Indonesian Biodiversity, 2020)
Abstract. Sidhiq DF, Subositi D, Widiyastuti Y, Pujiasmanto B, Yunus A. 2020. Morphological diversity, total phenolic and flavonoid content of Echinacea purpurea cultivated in Karangpandan, Central Java, Indonesia. Biodiversitas 21: 1265-1271. Purple coneflower (Echinacea purpurea (L.) Moench) is a medicinal plant introduced from North America. While it has been introduced to Indonesia long several decades ago. E. purpurea has not been developed as a raw material for herbal medicines in Indonesia as it faces constraints, namely non-uniform production and lack of information on the total phenolic and flavonoid content if cultivated in the country. This study aims to determine the morphological diversity, total phenolic and flavonoid content of three accession E. purpurea cultivated on lowland area (i.e. 493 m asl) in Tegalgede, Karangpandan, Central Java, Indonesia. This study used a Randomized Complete Group Design (RCBD) method with 1 factor, namely 3 accessions of E. Purpurea: A1, A2, A3 each with four replications. Morphological observations, as well as laboratory analysis, were done in this research to collect quantitative and qualitative data. The quantitative data were analyzed using SPSS to test the difference. We found there is significantly different results E. Purpurea accession in term of plant height, wet stover weight, number of leaves, root weight, root length, number of branches. Quantitative observation in the form of extract yield, total phenol content and total flavonoid highest content of extract residue produced by Accession 3 with 7,655%, while the highest phenolic was produced by Accession 1 with 507,619 mg GAE.g -1 extract, and the highest flavonoid was produced by Accession 2 with 313,869 mg QE.g-1 extract. This study concludes that there is morphological diversity of E. purpurea cultivated in Karangpandan with a significant correlation of accession to residue extract, phenolic, and flavonoid content.